Prevalence of Latent and Active Tuberculosis Infection in Inflammatory Bowel Disease Patients Who Received Biological Treatment - Dashdamirova, Saida; Eskazan, Tugce; Erzin, Yusuf Ziya; Celik, Aykut Ferhat; Hatemi, Gülen; Hatemi, Ali Ibrahim (Turkish Journal of Gastroenterology, 2026)
Background/Aims: This study aims to assess the frequency of latent tuberculosis (TB) and the incidence of active TB infection in patients with inflammatory bowel disease (IBD) and Behçet’s syndrome with gastrointestinal involvement who received either tumor necrosis factor–alpha (TNF-α) antagonist therapy or vedolizumab as a second-line biologic treatment following TNF-α antagonist therapy. Materials and Methods: A total of 349 patients were included in the study. Demographic data, disease characteristics, TB screening results, prophylactic treatment regimens and the duration, as well as side effects were collected from patient records. Results: Among the patients, 196 (56.1%) were male, with a mean age of 42 years and a mean disease duration of 10 Å} 6 years. A total of 267 (76.5%) had Crohn’s disease, 76 (21.8%) had ulcerative colitis, 3 had indeterminate colitis (0.8%), and 3 had Behçet’s syndrome with gastrointestinal involvement (0.8%). Latent TB was diagnosed in 176 (50.4%) patients, and 162 (92%) of them received isoniazid prophylaxis. Six (1.7%) patients developed active TB infection during the treatment period, occurring between 2 and 48 months after initiating TNF-α antagonist therapy. No cases of tuberculosis were observed in patients who had vedolizumab treatment. Among those who developed TB, 3 patients had pulmonary TB, and 3 had both pulmonary and extrapulmonary TB. No significant association was found between TB development and IBD phenotype or isoniazid use. Conclusion: Despite latent TB screening and prophylactic treatment, patients receiving TNF-α antagonists remain at risk of developing active TB, with a latent TB prevalence of 50.4% and an active TB incidence of 1.7%. These findings underscore the continued need for vigilance and robust TB monitoring strategies in this patient population. Cite this article as: Dashdamirova S, Eskazan T, Erzin YZ, et al. Prevalence of latent and active tuberculosis infection in inflammatory bowel disease patients who received biological treatment. Turk J Gastroenterol.Published online February 13, 2026. doi: 10.5152/tjg.2026.25072.